Integrated FMEA FTA HOR Reduces Production Defect Risk: Penerapan EOQ Mengurangi Biaya Persediaan PAC dalam Pengolahan Air - Indri Maulidiyah; Indah Apriliana Sari W. (Universitas Muhammadiyah Sidoarjo, 2025)
General Background Product quality and risk management are essential aspects of maintaining efficient production systems. Specific Background Many industries experience recurring defects due to inadequate identification and control of potential failure modes. Knowledge Gap However, the integration of multiple risk analysis methods to systematically address these issues remains limited. Aims This study aims to analyze and mitigate production risks using Failure Mode and Effect Analysis (FMEA), Fault Tree Analysis (FTA), and House of Risk (HOR). Results The findings identify critical failure modes with high risk priority values and reveal root causes through FTA. The HOR method prioritizes mitigation strategies, focusing on the most significant risk agents. Novelty This study integrates three analytical approaches to provide a comprehensive framework for quality improvement and risk mitigation. Implications The results offer practical guidance for reducing defects and improving decision-making in production risk management. Keywords: Failure Mode Analysis, Fault Tree Analysis, House Of Risk, Quality Control, Risk Mitigation Key Findings Highlights Critical failure sources identified through structured evaluation Root cause mapping clarifies defect occurrence pathways Priority-based actions guide targeted improvement strategies